Plasma Jet Sputtering as an Efficient Method for the Deposition of Nickel and Cobalt Mixed Oxides on Stainless-Steel Meshes: Application to VOC Oxidation - Jirátová, Květa; Čada, Martin; Naiko, Iryna; Ostapenko, Alina; Balabánová, Jana; Koštejn, Martin; Maixner, Jaroslav; Babii, Timur; Topka, Pavel; Soukup, Karel; Hubička, Zdeněk; Kovanda, František (Catalysts, 2023)
Hollow cathode plasma sputtering is an advantageous method of preparing catalysts in the form of thin oxide films on supports. Such catalysts are particularly suitable for processes such as catalytic total oxidation of volatile organic compounds (VOCs), representing an economically feasible and environmentally friendly method of VOC abatement. Catalysts with Ni:Co molar ratios of 1:4, 1:1, and 4:1 were prepared on stainless-steel meshes and compared with single-component Ni and Co oxide catalysts. The properties of the catalysts were characterized by EDX, SEM, powder XRD, temperature-programmed reduction (H2-TPR), Raman spectroscopy, and XPS. Powder XRD revealed the formation of various crystalline phases that were dependent on molar the Ni:Co ratio. NiO and Co3O4 were identified in the single-component Ni and Co oxide catalysts, whereas Ni-Co mixed oxides with a spinel structure, together with NiO, were found in the catalysts containing both Ni and Co. Raman spectra of the catalysts prepared at high working pressures showed a slightly lower intensity of bands, indicating the presence of smaller oxide particles. The TPR profiles confirmed the improved reducibility of the Ni-Co oxide catalysts compared to the single-component Ni and Co catalysts. Catalytic activity was investigated in the deep oxidation of ethanol and toluene, which were used as model volatile organic compounds. In ethanol oxidation, the activity of sputtered catalysts was up to 16 times higher than that of the commercial Cu-Mn oxide catalyst EnviCat® VOC-1544. The main benefits of the sputtered catalysts are the much lower content of Ni and Co oxides and a negligible effect of internal diffusion. Moreover, the process of plasma jet sputtering can be easily implemented on a large scale.